Identifikasi Cacat Prioritas pada Proses Shaving untuk Pengendalian Mutu Kualitas - Mahmud Basuki (JRSI (Jurnal Rekayasa Sistem dan Industri), 2019)
PT XYZ is a company engaged in leather tanning since 1966. The skin used by PT XYZ is sheep skin and goat skin, each of which has a composition of 50%. This study aims to analyze product defects in the process of shaving (tanning) by using statistical quality control and knowing the factors that cause product defects using Ishikwa diagrams. The results showed that there were three types of disabilities, namely tear, lorek, and thinness. By using the control chart p (p-chart) there are 5 out of control data observations with prioritization of repairs that must be done first is the type of tear, thinness, and finally lorek which analyzed the causes of product defects using Ishikawa diagram.